The Effects of Oil Prices and Oil Production on Non-Oil Exports in an Oil-Rich Country: The Case of Dutch Disease Symptom in Azerbaijan - Majidli, Famil (International Journal of Energy Economics and Policy, 2022)
The aim of the study is to examine whether there is a Dutch disease symptom by revealing the short-term and long-term effects of oil prices and oil production on non-oil exports in oil-rich Azerbaijan. In this context, ARDL bounds test and FMOLS method was applied by considering oil price, real GDP and non-oil real export variables covering the period 2001Q1 and 2019Q4. The results of the analysis determine that there is a cointegration relationship between the variables. Short-term and long-term coefficients are statistically indicated. In the long run, there is a positive relationship between non-oil real exports and oil prices, but a negative relationship between non-oil real exports and oil production. Especially the second finding can be associated with "resource movement effects", which is one of the symptoms of Dutch disease. The research can be described as original because it evaluates the Dutch disease phenomenon from the perspective of oil (abundant resource) production and because there are almost no similar studies in the literature in terms of examining the effect of oil production on non-oil exports in general. In addition, there is no common opinion in the literature about the presence of Dutch disease in Azerbaijan, in this context, results of this research, which offer a different perspective to test the presence of Dutch disease, provide valuable information.